2017
DOI: 10.1103/physrevb.95.224422
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic proximity coupling to Cr-doped Sb2Te3 thin films

Abstract: Using soft x-ray absorption spectroscopy we determined the chemical and magnetic properties of the magnetic topological insulator (MTI) Cr:Sb 2 Te 3 . X-ray magnetic circular dichroism (XMCD) at the Cr L 2,3 , Te M 4,5 , and Sb M 4,5 edges shows that the Te 5p moment is aligned antiparallel to both the Cr 3d and Sb 5p moments, which is characteristic for carrier-mediated ferromagnetic coupling. Comparison of the Cr L 2,3 spectra with multiplet calculations indicates a hybridized Cr state, consistent with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 44 publications
8
56
0
Order By: Relevance
“…The observed Sb 5p magnetic moment at the non-magnetic element is most likely induced by the V magnetic dopant. This result is in good agreement with the previous XMCD studies for Cr-or V-doped compounds [29,33,35,36,38]. More importantly, very small but clear XMCD signals are observed at the Te M 4,5 absorption edges.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The observed Sb 5p magnetic moment at the non-magnetic element is most likely induced by the V magnetic dopant. This result is in good agreement with the previous XMCD studies for Cr-or V-doped compounds [29,33,35,36,38]. More importantly, very small but clear XMCD signals are observed at the Te M 4,5 absorption edges.…”
Section: Resultssupporting
confidence: 92%
“…The microscopic origin of the ferromagnetism and the QAH state has been extensively investigated by theoretical and experimental approaches [26][27][28][29][30][31][32][33][34][35][36][37][38]. Element-specific x-ray absorption spectroscopy (XAS) and x-ray magnetic circular dichroism (XMCD) experiments revealed that the long-range ferromagnetic order in the magnetic TIs is caused by a magnetic coupling between p-d electrons of the host and magnetic dopants because the clear XMCD signals were observed not only at V (Cr) sites but also at Sb sites [29,33,35,36,38]. In addition, first principles calculations, scanning tunneling microscopy/spectroscopy (STM/STS) and resonant photoemission spectroscopy identified the impurity states of vanadium dopants at or near the Dirac node [26,30,32,36].…”
Section: Introductionmentioning
confidence: 99%
“…The XMCD at Fe L 3 and Te M 5 edges features opposite signs, pointing down for Fe L 3 and pointing up for Te M 5 . This reveals the FM coupled nature between these two elements defined by the inverse electronic transition symmetry, [14][15][16] which is discussed in the following paragraph. Figure 2(d) presents the full range XMCD survey across the Te M 4 and M 5 edges using r(þ) along with the result by r(À).…”
mentioning
confidence: 70%
“…2(c XMCD at the Te M 5 edge represents a magnetic moment on the Te's valence orbit 14,15 resulting from the interfacial orbital hybridization with Fe 3d or Tm 4f after introducing an adjacent TIG. Consequently, the opposite sign of XMCD at the Fe L 3 and Te M 5 edges at 20 K reveals that the magnetic moment on the Te 5p-orbit is FM coupled with Fe 3d 14,15 referring to their inverse electronic transition symmetry, 2p!3d for Fe L 3 and 3d!5p for Te M 5 . 14,15 Hence, Tm 4f and Te 5p are AFM coupled.…”
mentioning
confidence: 99%
“…This is comparatively two orders higher than bulk and epitaxial films of Bi 2 Se 3 and Bi 2 Te 3 [36]. Furthermore, higher concentration of Cr (x>0.20) supplies more free charge carriers in the form of holes in Bi 2 Te 3, Sb 2 Te 3 and electrons in Bi 2 Se 3 as a result of impregnable chemical potential disorder around the Dirac point [36,38]. We conclude that this scenario would be a descriptive of non-localized bulk carrier scattering rather than localized Dirac surface electrons in the vicinity of T c for this heterostructure.…”
Section: Resultsmentioning
confidence: 97%